Viabilitas kombinasi bakteri dan cendawan pada berbagai komposisi bahan pembawa dan efektifitasnya dalam mendekomposisi biomas jagung - Djaenuddin, Nurasiah; Faesal, Faesal; Syafruddin, Syafruddin (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
One alternative to accelerate the decomposition of lignin or cellulose organic matter is to use microorganisms. Bacterial  combined with fungi and synergistic will produce good compost. To ensure the viability and effectiveness of the decomposer microorganisms a suitable carrier material is required. The objective of the study were to obtain a combination of microorganisms isolates (bacteria and fungi) in accordance with the formulation of the carrier in supporting their viability and effectiveness to decomposting of maize biomass. The results showed that the combination of isolates  E7.7 + P7 and B7.1 + O5 up to 28 weeks' storage were relatively superior than Promi and EM4. At 28 weeks storage,  population of bacterial E7.7+P7  is 2,1-2,75x109 cfu/g and fungus  0,3-0,48x109 cfu/g, isolate B7.1+O5 had bacterial   1,38-2,5x109 cfu/g and fungus  0,2-0,3x109 cfu/g. While Promi and EM4 had bacterial were about 0.1-1.5x109 cfu/g and fungus 0.1x109 cfu/g. Both of these isolate   to decomposition of maize biomass had lower C/N and water content, and higher P and K content than EM4. Therefore, both of the combination of bacteria and fungi (E7.7 + P7 and B7.1 + O5) are worthy to biodecomposer for the making of compost fertilizer. To maintain viability and effectiveness of microbe E7.7+P7 was a better to use sago+compost, while for the combination of B7.1+O5 can using sago+compost and alternative is rice water+zeolit carrier material. The results of identification based on 16S rRNA sequence showed that isolates B7.1 and E7.7, respectively were Bacillus cereus strain ATCC14579 and Brevundimonas diminuta strain NBRC12967, while isolates of fungus O5 and P7 respectively were are Aspergillus fumigatus strains KARVSO4, and Aspergillus fumigatus strains DAOM-21534-28S.